The Stonewall Riots : making a stand for LGBTQ rights - Bongiovanni, Archie (History comics (First Second (Firm)), 2022)
Teens Natalia, Jax, and Rashad time travel to the Stonewall Inn in 1969, to experience the police raid and riots firsthand. Includes LGBTQ resources for youth and a glossary of LGBTQ terms.